A novel three-way rearrangement involving ETV6 (12p13) and ABL1 (9q34) with an unknown partner on 3p25 resulting in a possible ETV6-ABL1 fusion in a patient with acute myeloid leukemia: a case report and a review of the literature. Issue 1 (December 2016) - Tirado, Carlos; Siangchin, Ken; Shabsovich, David; Sharifian, Maryam; Schiller, Gary
Abstract Background Acute myeloid leukemia (AML) is commonly characterized by several chromosomal abnormalities resulting in the formation of chimeric genes that play various roles in leukemogenesis. Translocations resulting in theETV6-ABL1 fusion gene are rare in AML and other hematologic malignancies with only thirty-two previously reported cases in the literature, five of which were AML. Findings Herein, we report the case of a 73-year-old male with acute myeloid leukemia arising from MDS, negative forPDGFRA andPDGFRB, positive for bone marrow eosinophilia, rash, and marked fluid retention, which improved dramatically with imatinib therapy. Conventional cytogenetics revealed a t(3;9)(p25;q34), t(5;18)(q13;p11.2), and additional material of unknown origin at 12p11.2 in 2 out of 10 metaphases analyzed. Interphase FISH studies showed evidence ofETV6 (12p13) andABL1 (9q34) rearrangements in 41.3 % and 5.7 % of the cells respectively. FISH studies on previously G-banded metaphases showed colocalization ofABL1 andETV6 signals to the short arm of chromosome 3 at 3p25 suggesting a possibleETV6-ABL1 fusion. Subtelomeric metaphase FISH studies also showed the presence of a subtelomere 3p signal on the long arm of the derivative 9, and no subtelomere 3p signal on the derivative chromosome 12. Conclusions These findings suggest a complex rearrangement involving an insertion ofETV6 into 3p25 followed by a reciprocal translocation involving 3p25 and 9q34, resulting in a possibleETV6-ABL1 fusion. This case highlights the importance of FISH to characterize complex rearrangements in myeloid malignancies, particularly those resulting in clinically significant chimeric genes.